Agrin Promotes Coordinated Therapeutic Processes Leading to Improved Cardiac Repair in Pigs. Issue 9 (1st September 2020) - Baehr, Andrea; Umansky, Kfir Baruch; Bassat, Elad; Jurisch, Victoria; Klett, Katharina; Bozoglu, Tarik; Hornaschewitz, Nadja; Solyanik, Olga; Kain, David; Ferraro, Bartolo; Cohen-Rabi, Renee; Krane, Markus; et al.
Abstract : Background: Ischemic heart diseases are leading causes of death and reduced life quality worldwide. Although revascularization strategies significantly reduce mortality after acute myocardial infarction (MI), a large number of patients with MI develop chronic heart failure over time. We previously reported that a fragment of the extracellular matrix protein agrin promotes cardiac regeneration after MI in adult mice. Methods: To test the therapeutic potential of agrin in a preclinical porcine model, we performed ischemia–reperfusion injuries using balloon occlusion for 60 minutes followed by a 3-, 7-, or 28-day reperfusion period. Results: We demonstrated that local (antegrade) delivery of recombinant human agrin to the infarcted pig heart can target the affected regions in an efficient and clinically relevant manner. A single dose of recombinant human agrin improved heart function, infarct size, fibrosis, and adverse remodeling parameters 28 days after MI. Short-term MI experiments along with complementary murine studies revealed myocardial protection, improved angiogenesis, inflammatory suppression, and cell cycle reentry as agrin's mechanisms of action. Conclusions: A single dose of agrin is capable of reducing ischemia–reperfusion injury and improving heart function, demonstrating that agrin could serve as a therapy for patients with acute MI and potentially heart failure. Abstract : Supplemental Digital Content is available in the text.